2013
DOI: 10.1080/14786419.2012.662647
|View full text |Cite
|
Sign up to set email alerts
|

New triterpenoids from the stem bark ofHypodaphnis zenkeri

Abstract: A new pentacyclic triterpenoid and three new derivatives based on the taraxer-14-ene skeleton with a C-28 attached a carboxylic acid group have been isolated from the stem bark of Hypodaphnis zenkeri, together with six known compounds. The new product was identified as 2α,3α-dihydroxytaraxer-14-en-28-oic acid (1). Its derivatives, 2α,3α-diacetyltaraxer-14-en-28-oic acid (2), 2α,3α-di-O-carbonyl-2α,3α-dihydroxytaraxer-14-en-28-oic acid (3) and 2α,3α-dipropionyltaraxer-14-en-28-oic acid (4) were obtained by semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…H. zenkiri is a tree reaching a height of 20 to 25 m [22,23]. Its bark is consumed as a spice in Cameroon and is also used in traditional medicine [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. zenkiri is a tree reaching a height of 20 to 25 m [22,23]. Its bark is consumed as a spice in Cameroon and is also used in traditional medicine [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Its bark is consumed as a spice in Cameroon and is also used in traditional medicine [23,24]. The aqueous/ethanol extract of the bark of H. zenkiri have been postuled to possess quinones, tannins, terpenoids and reducing sugars with a great polyphenolic content and an antioxidant power in the 2,2-azinobis(3-ethylbenzthiazoline)-6-sulfonic acid (ABTS) assay [22,23,24]. A previous study demonstrated that the bark of H. zenkiri lowered blood glucose and ameliorated the lipid profile in triton W-1339 induced acute hyperlipidemic rats and rats fed with a high fat and high glucose diet [23].…”
Section: Introductionmentioning
confidence: 99%
“…The above information revealed that compound 1 should be a pentacyclic triterpenoid. Comparison of the NMR data ( Table 1) with those of 2,3-dihydroxytaraxer-14-en-28-oic acid (Momo et al, 2013) indicated that 1 is a taraxeren skeleton possessing an acetyl group, a trans-p-hydroxycinnamoyl group and a carboxylic group at C-28. In the HMBC spectrum, the correlations from H-3 (d H 5.09) to C-9 0 (d C 167.2) of the trans-phydroxycinnamoyl group suggested the trans-p-hydroxycinnamoyl group was positioned at C-3 by an oxygen atom.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, only non-volatile chemical information about the species has been reported in the stem bark and leaves of the Hypodaphnis zenkeri (Momo et al 2013, Moukette et al 2014. Therefore, this study aims to document the cuticular characters of the plant which hitherto is lacking and provide additional chemical characters that partly underlie the medicinal usefulness of the plant.…”
Section: Introductionmentioning
confidence: 99%